The analysis of safety and traffic conditions on Orląt Lwowskich Square in Wrocław - Wojciech Szczepanek (Przegląd Komunikacyjny)
Abstract: For some years road infrastructure has been beeing rebuilt and expanded in Wrocław. There are a lot of enterprises connected with it which aim is to encourage citizens to use public transport and also improve traffic conditions in the area of the whole city and adjust it to modern standards. This article refers to the analysis of the influence of the newly built. "TAT" rout level 1 in Wrocław on conditions in The Orląt Lwowskich square area. All elements which were rebuit, not only because of the new tramway but also because of regarded changes due to safety and increasing of road capacity, were taken under considaration. The condition before rebuilding, implemented changes and other ideas which could be applied were analysed. In the summary of this article advantages and disadvantages of individual solutions were presented with their description. Keywords: Traffic analysis; Safety; Road capacity; Tramway; Rebuilding; Traffic conditions